MYB8 controls inducible phenolamide levels by activating three novel hydroxycinnamoyl-coenzyme A: polyamine transferases in Nicotiana attenuata - Onkokesung, Nawaporn; Gaquerel, Emmanuel (Plant physiology, 2011)
A large number of plants accumulate N-acylated polyamines (phenolamides [PAs]) in response to biotic and/or abiotic stress conditions. In the native tobacco (Nicotiana attenuata), the accumulation of two major PAs, caffeoylputrescine and dicaffeoylspermidine (DCS), after herbivore attack is known to be controlled by a key transcription factor, MYB8. Using a broadly targeted metabolomics approach, we show that a much larger spectrum of PAs composed of hydroxycinnamic acids and two polyamines, putrescine and spermidine, is regulated by this transcription factor. We cloned several novel MYB8-regulated genes, annotated as putative acyltransferases, and analyzed their function. One of the novel acyltransferases (AT1) is shown to encode a hydroxycinnamoyl-coenzyme A:putrescine acyltransferase responsible for caffeoylputrescine biosynthesis in tobacco. Another gene (acyltransferase DH29), specific for spermidine conjugation, mediates the initial acylation step in DCS formation. Although this enzyme was not able to perform the second acylation toward DCS biosynthesis, another acyltransferase gene, CV86, proposed to act on monoacylated spermidines, was isolated and partially characterized. The activation of MYB8 in response to herbivore attack and associated signals required the activity of LIPOXYGENASE3, a gene involved in jasmonic acid (JA) biosynthesis in N. attenuata. These new results allow us to reconstruct a complete branch in JA signaling that defends N. attenuata plants against herbivores: JA via MYB8’s transcriptional control of AT1 and DH29 genes controls the entire branch of PA biosynthesis, which allows N. attenuata to mount a chemically diverse (and likely efficient) defense shield against herbivores.